Student’s obstacles in learning surface area and volume of a rectangular prism related to mathematical representation ability - Safitri, Gita; Darhim, Darhim; Dasari, Dadan (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
The surface area and volume of cubes and cuboids are mathematical concepts related to everyday life. However, many students need help learning this concept. This study aims to analyze the learning obstacles junior high school students encounter when solving mathematical representation problems on the concept of surface area and volume of cubes and cuboids. This study uses an interpretive paradigm which is part of Didactical Design Research (DDR). Students at one of the public junior high schools in Jambi City were given six questions related to mathematical representation after the researchers conducted classroom observations, which were then followed by interviews with students with high, moderate, and low representation abilities. Data analysis techniques include data reduction, display, and conclusion drawing and verification. The results showed that students experienced three learning obstacles: ontogenic, epistemological, and didactical. Furthermore, the results of this study can be a consideration for teachers to create learning designs for surface area and volume of cubes and cuboids that can anticipate student learning obstacles and develop students' mathematical representation abilities.